Meteorite evidence for partial differentiation and protracted accretion of planetesimals - Bryson, J; Maurel, C; Lyons, R; Ball, M; Chopdekar, R; Scholl, A; Ciesla, F; Bottke, W; Weiss, B (American Association for the Advancement of Science, 2020)
Modern meteorite classification schemes assume that no single planetary body could be source of both unmelted (chondritic) and melted (achondritic) meteorites. This dichotomy is a natural outcome of formation models assuming that planetesimal accretion occurred nearly instantaneously. However, it has recently been proposed that the accretion of many planetesimals lasted over ≳1 million years (Ma). This could have resulted in partially differentiated internal structures, with individual bodies containing iron cores, achondritic silicate mantles, and chondritic crusts. This proposal can be tested by searching for a meteorite group containing evidence for these three layers. We combine synchrotron paleomagnetic analyses with thermal, impact, and collisional evolution models to show that the parent body of the enigmatic IIE iron meteorites was such a partially differentiated planetesimal. This implies that some chondrites and achondrites simultaneously coexisted on the same planetesimal, indicating that accretion was protracted and that apparently undifferentiated asteroids may contain melted interiors.